Financial Risks and Financial Performance Nexus with Moderating Role of Bank’s Capital: Evidence from Commercial Banks of Pakistan - Sadia Saeed Corresponding Author; Fauzia Mubarik; Shehla Akhtar; Shazia Hassan; Aliya Jalil (Al-Qanṭara, 2023)
In this study, financial risks and financial performance have been empirically explored in relation to the moderating function of a bank's capital. In panel data sets during a time period (2010-2020), the generalised Method of Moments (GMM) dynamic model has been used to provide results that are resistant to bias in the context of heteroskedasticity, autocorrelation, cross-sectional dependency, and temporal dependence.. After controlling bank-specific factor efficiency, The empirical results show a substantial correlation between the financial performance of commercial banks listed on the Pakistan Stock Exchange and financial risk indicators, including liquidity risk, market risk, and credit risk Furthermore, the influence of financial risks on financial health is moderated by the Bank's capital. Alternative measures of financial performance are selected to robust the results. The study’s findings imply that policymakers should incorporate all the financial risks while designing strategies for improving financial performance, especially with raising funds for investment.